Physiological and biochemical adaptive responses and defense mechanisms to withstand increasing ultraviolet radiation and temperatures in an Antarctic meiofauna organism. - GIOVANNINI, ILARIA; GUIDETTI, Roberto; ALTIERO, Tiziana; CESARI, Michele; BERTOLANI, Roberto; REBECCHI, Lorena; Montorfano, G.; Rizzo, A. M. (Lino Ometto, Omar Rota-Stabelli, 2013)
Physiological and biochemical adaptive responses and defense mechanisms to withstand increasing ultraviolet radiation and temperatures in an Antarctic meiofauna organism.